Comprehensive analysis of tool wear, tool life, surface roughness, costing and carbon emissions in turning Ti–6Al–4V titanium alloy: Cryogenic versus wet machining. (January 2021) - Agrawal, Chetan; Wadhwa, Jwalant; Pitroda, Anjali; Pruncu, Catalin Iulian; Sarikaya, Murat; Khanna, Navneet
Abstract: Cryogenic machining has emerged as a sustainable technique that reflects in terms of reduced environmental effects, superior part quality, and lesser resource consumption. However, further exploration of machinability and sustainability improvements using this technique will help the manufacturing industry to adopt it as an alternative to conventional techniques. In this government-supported work, the machinability of Ti–6Al–4V is assessed at five different cutting speeds (70, 80, 90, 100, and 110 m/min) under wet and cryogenic environments. This article presents a detailed analysis of tool wear (flank and crater wear), power consumption, and surface roughness to seek improvements in machinability of Ti–6Al–4V using cryogenic turning in comparison to wet turning. To investigate the sustainability aspects of cryogenic and wet turning, results are also analyzed in terms of total machining cost and carbon emissions that remain relatively less explored in literature. The results show higher crater wear under a wet environment relative to the cryogenic environment at most of the cutting speeds. However, tool life is improved (by up to 125%) using cryogenic turning in comparison to wet turning exclusively at higher cutting speeds (100 and 110 m/min). Reduced power consumption (by up to 23.4%) and surface roughness (by up to 22.1%) are obtained using cryogenic turning than wet turning at all cutting speeds. It is noted that machining cost is reduced (by up to 27%) using cryogenic turning in comparison to wet turning, especially at higher cutting speeds. Cryogenic turning is proved to be better in terms of environmental aspects as it enables a reduction in overall carbon emissions (by up to 22%) at higher cutting speeds.